Individuals Time Preference and Social Discounting: A Survey and a Meta-Analysis - Marco Percoco; Peter Nijkamp (European Regional Science Association (ERSA), 2006)
The choice of an appropriate social rate of discount is critical in the decision-making process on public investments. In this paper we review concisely the literature on social discounting and refer explicitly to a recently growing field of related research, that is, individual time preference. The consideration and analysis of behavioural factors of individuals in the definition and use of an appropriate social discount rate are critical for balanced decision-making, for example, in the field of environmental policy. The empirical literature shows quite some variation in the estimated values of individual discount rates. Therefore, we present results from a meta-analysis conducted over more than 40 experimental and field studies reporting individual discount rate estimates. We find that the experimental design of a study has a great impact on these estimates and conclude that our meta-regression function has a low transfer value.
Keywords: 330